Implementation of Leadership Style Principal's Impact on Teacher Performance in Increase Performance Students at Kartika 1-2 High School Medan - Ibrahim Vagoh Ginting; Eli Delvi Yanti (Journal of Research in Social Science and Humanities, 2026)
This study analyzes how the leadership style of school principals plays a role in improving teacher performance and its impact on student achievement at Kartika 1–2 High School in Medan. The researchers used an associative quantitative approach involving all teachers as respondents through saturated sampling techniques. Research data were obtained through questionnaires and processed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results of the analysis show that principals who implement effective leadership styles are able to significantly improve teacher performance. In addition, improvements in teacher performance have also been proven to contribute directly to improvements in student achievement. This confirms that the leadership style of the principal and teacher performance are two important interrelated factors in efforts to improve student learning outcomes